2017
DOI: 10.19044/esj.2017.v13n31p317
|View full text |Cite
|
Sign up to set email alerts
|

Employee Engagement, Organisational Commitment and Performance of Selected State Corporations in Kenya

Abstract: The influence of employee engagement on organisational performance has been widely acknowledged and confirmed. However, there are scanty empirical investigations on the mediating role of organisational commitment on the relationship between employee engagement and organisational performance. Therefore, this study sought to investigate the mediating influence of organisational commitment on the relationship between employee engagement and performance of selected state corporations in Kenya. The study adopted a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Therefore, the engagement is ranked as the third significant factor affecting the success of Kaizen implementation ( =0.811) which is similar to the finding by Stadnicka & Sakano [112]. It is also ranked the fourth in affecting the sustainable performance ( =0.811), further agreeing with [182,[184][185][186][187][188][189][190][191][192][193]. Basically, the engagement from management levels can refer to their supports and commitments, whereas the engagement from employees refers to their participation in relevant activities with their responsibility.…”
Section: Complexitysupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, the engagement is ranked as the third significant factor affecting the success of Kaizen implementation ( =0.811) which is similar to the finding by Stadnicka & Sakano [112]. It is also ranked the fourth in affecting the sustainable performance ( =0.811), further agreeing with [182,[184][185][186][187][188][189][190][191][192][193]. Basically, the engagement from management levels can refer to their supports and commitments, whereas the engagement from employees refers to their participation in relevant activities with their responsibility.…”
Section: Complexitysupporting
confidence: 81%
“…Moreover, they tend to be more satisfied with their jobs, committed, and loyal to their organizations [181] because they believe that they constitute a part of the organization [182]. Siddhanta & Roy [183] found that engagement makes employees more motivated and committed; thus, it positively affects organizational performance [182,[184][185][186][187][188][189][190][191][192][193]. Hence, engaged employees tend to proactively and enthusiastically participate in assigned activities with their full responsibilities.…”
Section: Engagementmentioning
confidence: 99%
“…Social relationship are based on the sense of reciprocity between the parties involved such that individuals have expectations from the organization which may include fair and adequate rewards, career opportunities, job security and emotional support (Eisenberger et al, 1986). In reference to SET, Cheche et al (2017) posit that human beings socially tend to conduct themselves in ways that will enable them maximally attaining their personal interests. This means that if the social set up is beneficial employees will reciprocate positively if otherwise negatively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This assertion is supported by Schaufeli (2013) who states that when the organization provides to the employees resources such as good pay, recognition, and development opportunities they would reciprocate positively towards the organization. SET is thus applicable in employee engagement studies since it considers reciprocal relationship between employers and employees (Cheche, Muathe & Maina, 2017).…”
Section: Review Of Literature Theoretical Reviewmentioning
confidence: 99%